Experiência moral no pensamento de Paul Ricoeur: elementos para uma gênese da “pequena ética” - Cunha, Wanderley Martins da (2017)
This work, based on the problem of elucidating the foundations and conditions of possibility of moral experience, aims to explore the various historical and conceptual stages of Ricoeur's philosophical itinerary in order to analyze his ethical project, by detecting, with their genesis, how it was structured and some of its implications. In the first part (THE INCHOATION OF ETHICAL REFLECTION IN THE PHILOSOPHY OF WILL) ─ within the framework of the realization of his first philosophical project, Ricoeur unravels the horizon of a real ethic, namely, a reflection on concrete moral experience, in which, however, because of its methodological choice, can not penetrate ─ seeks to demonstrate how a tension between the imperative and the optative is already present from the first movements of reflection ethics of Paul Ricoeur, since the philosopher accesses the ethical domain both through the golden path of Kantian respect, in confrontation with the limits of the phenomenological approach to the problem of the constitution of otherness, and through the appropriation of an non-deontological model of Nabertian inspiration based on originating affirmation and in the desire to be. In the second part (THE INFLEXIONS OF ETHICAL REFLECTION IN THE HERMENEUTICAL ITINERARY OF PAUL RICOEUR) ─ it has been found that it will be in the wake of the programmatic content that the philosopher had predicted for a future empirical of the will that steps could be taken in the direction of a concrete morality or of a real ethic, announced but not developed in its philosophy of the will ─, it is intended to demonstrate that, due to the multiple deviations by which the development of the thought of Ricoeur would happen in the years following the publication of Symbolic of Evil, such route was made gradually and not entirely systematically. In the third part (RICOEURIAN ETHICS REFLECTION IN THE HORIZONT OF THE PHENOMENOLOGY OF THE CAPABLE MAN), we try to show how Ricoeur's ethical reflections developed in previous decades receive, from the 1990s, "in its Little Ethics", a new formulation that, without denying its foundations, advances ricoeurian thought in the direction of contemporary ethical problems, while at the same time realizing the intention, present since the beginning of the philosophical itinerary of Ricoeur, to construct a "real ethics", this is, a reflection on concrete moral experience